Connection Between Oral Behaviors and Pain Intensity in Temporomandibular Disorder Patients Undergoing Orthodontic Treatment: A Cross-Sectional Study - Zihan Zhang; Li Zhang; Yanyu Sun; Rongrong Huo; Yanyue Tan; Fan He; Jun Wang; Shufang Du; Xin Xiong (International Journal of Clinical Practice)
Proper management of painful temporomandibular disorders (PTMDs) is important for guaranteeing optimal orthodontic outcomes. Although correlations between oral behaviors and PTMDs have been confirmed in the general population, there is limited corresponding research within the orthodontic patients. The purpose of this cross-sectional study was to examine how pain intensity correlates with the frequency of various oral behaviors in orthodontic patients. Participants completed a questionnaire survey containing demographic details, an eight-item oral behaviors checklist, the five major temporomandibular disorders symptoms (5Ts) checklist, and a visual analog scale (VAS) to gauge pain intensity. Participants were divided into two groups: PTMD and without PTMD (NPT). The correlation between specific oral behaviors and pain intensity was assessed using both univariate and multivariate linear regression analyses, with adjustment for demographic variables such as age, gender, systemic diseases, and level of education. The study gathered 267 valid questionnaires, showing a prevalence of 59.93% for PTMD. In comparison to the NPT group, the PTMD group exhibited a higher frequency of oral behaviors. Significant correlations were identified between various oral behaviors and pain intensity. Univariate and multivariate linear regression analyses demonstrated positive relationships between pain and oral behaviors. After adjusting for demographic variables, these connections remained statistically significant in the multivariate analysis for sleep bruxism (β = 0.17; 95% CI 0.03, 0.31; p=0.0175), sleep position pressuring jaw (β = 0.15; 95% CI 0.03, 0.26; p=0.0118), awake bruxism (β = 0.57; 95% CI 0.26, 0.88; p=0.0004), and holding, tightening, or tensing muscle without clenching (β = 0.18; 95% CI 0.01, 0.36; p=0.0415). A significant association was identified between the frequency of oral behaviors and pain intensity in orthodontic patients. Screening and management of oral behaviors might be crucial for controlling TMDs during orthodontic treatment.